2008
DOI: 10.1093/ndt/gfn733
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis patients' readiness to pursue live donor kidney transplantation

Abstract: Tailored educational programmes considering the patient's stage of readiness and related attitudinal and demographic factors might help patients move towards LDKT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Similar to study participants reporting that their "doing fine on dialysis" was a concern about pursuing KT, patients undergoing dialysis have previously reported that the social and emotional support from the dialysis community is an advantage to remaining on dialysis (9). Furthermore, with 29.9% of participants reporting that they did not feel comfortable asking a living person to donate a kidney, our results are consistent with studies of prevalent dialysis patients and waitlisted patients reporting reluctance to talk to others about live donation (8,34,35). In addition, the association between less education and high levels of concerns observed among our study population is consistent with documented decreased access to KT among those with less education (36,37).…”
Section: Discussionsupporting
confidence: 87%
“…Similar to study participants reporting that their "doing fine on dialysis" was a concern about pursuing KT, patients undergoing dialysis have previously reported that the social and emotional support from the dialysis community is an advantage to remaining on dialysis (9). Furthermore, with 29.9% of participants reporting that they did not feel comfortable asking a living person to donate a kidney, our results are consistent with studies of prevalent dialysis patients and waitlisted patients reporting reluctance to talk to others about live donation (8,34,35). In addition, the association between less education and high levels of concerns observed among our study population is consistent with documented decreased access to KT among those with less education (36,37).…”
Section: Discussionsupporting
confidence: 87%
“…Our study has a number of strengths, but we acknowledge possible limitations related to generalizability and bias. Unlike many prior studies, ours had a prospective design enabling the measurement of diverse participant characteristics such as knowledge that could predict subsequent ability to attract a donor or undergo live donor transplantation (9,35,36). With reference to generalizability, participants were recruited from a center that performs approximately 110 deceased donor and 60 live donor transplants per year, has a racially diverse population, and draws patients from urban and rural areas in the northeastern United States.…”
Section: Predictors Of Having a Potential Live Kidney Donormentioning
confidence: 99%
“…2009). However, the hope of a transplant is often undermined by feelings of uncertainty and anxiety in relation to the potential complications of the procedure (Polaschek 2000, Pradel et al. 2009).…”
Section: Introductionmentioning
confidence: 99%